Fire-resistant and ablation-resistant and thermal shock-resistant composite coating, and preparation method and application thereof
Patent Information
- Application Number
- CN202611492601.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
在前期的研究的资料中,就提及了一种新型的玻璃/Si3N4复合涂层,其发现采用Si3N4作为内层可以在一定程度上提高其抗氧化性能,降低与基体热膨胀系数的差距以减缓热应力集中现象,但对于超高温(超过2000℃)的极端环境,其抗热震、耐烧蚀性能有待进一步提升
Smart Images

Figure CN122977872A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of surface coating technology, specifically relating to a fire-resistant, ablation-resistant, and thermal shock-resistant HfC coating. x N y -TaC-B4C-SiC / Si3N4 coating, its preparation method and application. Background Technology
[0002] Carbon / carbon composites (C / C) are a unique form of carbon fiber reinforced material, considered one of the most promising candidates for thermal insulation applications due to their lightweight, low thermal conductivity, and high-temperature resistance. However, their high sensitivity to high-temperature oxidation (above 400°C) and relatively harsh service environments significantly limit their application at high temperatures. The widely used coating technology works by coating the composite with advanced materials possessing good oxidation resistance to isolate oxygen from the carbon matrix, thereby improving the composite's oxidation and ablation resistance. Furthermore, it has proven to be the most effective and direct means of improving oxidation and ablation resistance without altering the material's mechanical properties.
[0003] Silicon-based ceramic coatings, as excellent antioxidant coatings, have been considered the most important candidate for providing effective protection for C / C composites over a wide temperature range. The most widely used and researched silicon-based coating is SiC coating (coefficient of thermal expansion: 4.5 × 10⁻⁶). -6 K -1 Due to its compatibility with the C / C matrix (coefficient of thermal expansion: 1.0 × 10⁻⁶), -6 K -1 SiC, with its matching coefficient of thermal expansion and low oxygen permeability, is widely used as a transition layer in composite coatings due to its oxidation product SiO2. However, SiC coatings exhibit severe volatilization in high-temperature environments exceeding 1500°C, failing to effectively repair cracks and hindering oxygen diffusion, thus leading to substrate failure. Therefore, it is necessary to find a transition layer to replace SiC coatings. Previous research has mentioned a novel glass / Si3N4 composite coating, which found that using Si3N4 as an inner layer can improve its oxidation resistance to some extent and reduce the difference in thermal expansion coefficient with the substrate to mitigate thermal stress concentration. However, for extreme environments with ultra-high temperatures (exceeding 2000°C), its thermal shock resistance and ablation resistance need further improvement. Furthermore, in the patent with publication number CN114605173A, it was found that although the combination of glass coating and HaC-TaC-B4C-SiC high-entropy coating has excellent oxidation resistance and good ablation resistance, the glass coating has always had an unsolvable problem of insufficient heat capacity, which makes it unable to adapt to extreme environments with ultra-high temperature (above 2000℃). Summary of the Invention
[0004] To address the above problems, based on previous research, this invention proposes a novel fire-resistant, ablation-resistant, and thermal shock-resistant HfC material. x N y -TaC-B4C-SiC / Si3N4 coating protection system. It uses Si3N4 instead of the traditional SiC transition layer and employs high-melting-point HfC doping. x N y A modified TaC-B4C-SiC coating system was developed to construct a composite coating with excellent ablation and thermal shock resistance. The Si3N4 transition layer designed in this invention exhibits superior oxidation resistance and a low coefficient of thermal expansion (approximately 3.77 × 10⁻⁶). -6 K -1 ); outer HfC x N y The TaC-B4C-SiC coating exhibits excellent high-temperature stability and outstanding ablation resistance. HfC coatings with good long-term antioxidant protection, excellent thermal shock and ablation resistance, and refractory properties were prepared by nitriding embedding combined with slurry brush coating and sintering. x N y -TaC-B4C-SiC / Si3N4 coating.
[0005] This invention discloses a fire-resistant, ablation-resistant, and thermal shock-resistant composite coating, which consists of a C / C matrix material, a Si3N4 transition layer, and HfC. x N y The structure consists of a TaC-B4C-SiC ceramic coating, with the following layers arranged outwards from the surface of the C / C substrate: a Si3N4 transition layer and an HfC layer. x N y -TaC-B4C-SiC ceramic coating; the raw materials used for the Si3N4 transition layer are α-Si3N4, Si, Al2O3, Y2O3, and phenolic resin solution; the HfC x N y The raw material used for the TaC-B4C-SiC ceramic coating is HfC. x N y TaC, B4C, SiC, and phenolic resin solution.
[0006] As a preferred embodiment, the raw materials used for the Si3N4 transition layer are α-Si3N4, Si, Al2O3, Y2O3, and a phenolic resin solution; wherein the mass ratio of α-Si3N4, Si, Al2O3, and Y2O3 is 35~65:55~25:6:4; α-Si3N4, Si, Al2O3, and Y2O3 form a mixed powder, and the mass ratio of the mixed powder to the phenolic resin solution is 1:3~5. In this invention, controlling the mass ratio of α-Si3N4, Si, Al2O3, and Y2O3 to 35~65:55~25:6:4 is because the powder content ratio plays an important role in the microstructure, phase composition, and overall thermal protection performance of the Si3N4 coating. If the content of any one or more of the components α-Si3N4, Si, Al2O3, and Y2O3 is too high, it will lead to problems such as high sintering temperature, high porosity, and many crack defects. If the content of any one or more of the components α-Si3N4, elemental silicon, Al2O3, and Y2O3 is too low, it will lead to problems such as an imbalance in the α / β-Si3N4 phase composition ratio and low interfacial bonding strength.
[0007] As a further preferred embodiment, the mass ratio of the raw materials α-Si3N4, Si, Al2O3, and Y2O3 used in the Si3N4 transition layer is 44~46:44~46:6:4; the mass ratio of the mixed powder composed of α-Si3N4, Si, Al2O3, and Y2O3 to the phenolic resin solution is 1:3.5~4.5. The phenolic resin solution is composed of phenolic resin and anhydrous ethanol in a mass ratio of 1:3.5~4.
[0008] As a further preferred embodiment, the mass ratio of the raw materials α-Si3N4, Si, Al2O3, and Y2O3 used in the Si3N4 transition layer is 45:45:6:4; and the mass ratio of the mixed powder composed of α-Si3N4, Si, Al2O3, and Y2O3 to the phenolic resin solution is 1:4.
[0009] As a preferred embodiment, the α-Si3N4, Si, Al2O3, and Y2O3 powders used in this invention have an average particle size of 1~10μm and a purity of not less than 99.5%.
[0010] As a preferred embodiment, the HfC x N y The raw material used for the TaC-B4C-SiC ceramic coating is HfC. x N y TaC, B4C, SiC, and phenolic resin solution; including HfC x N y The molar ratio of TaC and B4C is 1~3:3~1:3~1; HfC x N yThe mass ratio of the mixed powder composed of TaC and B4C to the SiC and phenolic resin solution is 1:1:1.5~3. This invention controls HfC. x N y The molar ratio of TaC and B4C is 1~3:3~1:3~1, and HfC is controlled. x N y The mass ratio of the mixed powder composed of TaC and B4C to the SiC and phenolic resin solution is 1:1:1.5~3. This is because the raw material ratio within the controlled range is conducive to the formation of Hf6Ta2O. 17 A stable, dense, and high-temperature resistant Hf-Ta-Si-O protective network, primarily composed of HfO2, Ta2O5, and SiO2 (with melting point > 2400 ℃ and no phase change between room temperature and melting point), is used as a secondary component. This reduces problems such as excessive phase change volume, insufficient high-melting-point oxides with high temperature resistance, and excessively rapid evaporation of low-melting-point liquid phases, which can lead to poor thermal protection performance of the coating. If the proportion of any one or more components among TaC, B4C, and SiC is too high, it will affect the thermal shock resistance and high-temperature ablation resistance of the product. The phenolic resin solution is composed of phenolic resin and anhydrous ethanol in a mass ratio of 1:3.5~4.
[0011] As a preferred option, the HfC used x N y In the powder, the carbon-nitrogen molar ratio is 54~72:46~28.
[0012] As a further preferred embodiment, the raw material used in the HfCxNy-TaC-B4C-SiC ceramic coating is HfC. x N y The molar ratio of TaC and B4C is 1:3:3; HfC x N y The mass ratio of the mixed powder composed of TaC and B4C to the SiC and phenolic resin solution is 1:1:2. The HfC used... x N y The carbon-nitrogen molar ratio in the powder is 64:36.
[0013] As a further preferred embodiment, the raw material used in the HfCxNy-TaC-B4C-SiC ceramic coating is HfC. x N y The molar ratio of TaC and B4C is 1:1:1; HfC x N y The mass ratio of the mixed powder composed of TaC and B4C to the SiC and phenolic resin solution is 1:1:2. The HfC used... x N y The carbon-nitrogen molar ratio in the powder is 64:36.
[0014] As a preferred embodiment, the HfC used in this invention x N y The average particle size of TaC, B4C, and SiC powders is 1~10μm, and the purity is not less than 99.9%.
[0015] This invention discloses a method for preparing a fire-resistant, ablation-resistant, and thermal shock-resistant composite coating, comprising the following steps:
[0016] Step 1, Matrix Pretreatment
[0017] Sand the C / C substrate with sandpaper, chamfer the edges, ultrasonically clean with anhydrous ethanol and dry for later use.
[0018] Step 2, Prepare Si3N4 transition layer
[0019] The raw materials of the Si3N4 transition layer, weighed according to the design composition, are mixed evenly and a slurry suspension is prepared. Specifically, phenolic resin and anhydrous ethanol are prepared in a mass ratio of 1:4 to form a phenolic resin solution. Then, the α-Si3N4, Si, Al2O3 and Y2O3 mixed powder obtained by ball milling for 10-12 hours and sieving through a 200-mesh sieve is added to the phenolic resin solution and then evenly dispersed by a magnetic stirrer to form a slurry suspension.
[0020] The slurry was uniformly brushed onto the C / C substrate after the pretreatment in step 1. After drying, it was placed in an oven at 150~200℃ for 3-6 hours to cure. Then, the cured sample was placed in Si3N4 embedding powder and kept at 1450~1650℃ in a nitrogen atmosphere for 2-3 hours to obtain a porous Si3N4 transition layer.
[0021] Step 3, prepare HfC x N y -TaC-B4C-SiC ceramic coating
[0022] HfC weighed according to the design composition x N y The raw materials for the TaC-B4C-SiC ceramic coating are mixed evenly to form a slurry suspension. The Si3N4 transition layer prepared in step 2 is immersed in the slurry suspension, removed, and dried. Then, it is cured in an oven at 150~200℃ for 3-6 hours. Subsequently, the cured sample is pyrolyzed at 650~750℃, preferably 700℃, for 2-3 hours. Finally, the pyrolyzed sample is held at 1900℃~2100℃ in a nitrogen atmosphere for 2-3 hours to obtain a smooth HfC. x N y -TaC-B4C-SiC ceramic coating.
[0023] In industrial applications, the Si3N4 transition layer prepared in step 2 is immersed in a slurry suspension. The immersion time and number of immersions are controlled according to the surface quality, followed by removal, drying, and then curing. Preferably, the immersion time for a single immersion is 1-3 minutes, and the number of immersions is 1-5 times.
[0024] The resulting coated samples were subjected to isothermal oxidation testing in air at 1500℃ for 200 hours, and the mass change rate was less than or equal to 2.62%. The optimal sample could protect the C / C composite material against oxygen erosion for 412 hours with a mass loss rate of only 0.98%.
[0025] In this invention, the obtained coating sample was placed in an air environment at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the sample, cooling it at room temperature for 5 minutes, and then weighing it; this cycle was repeated. After 20 thermal shock cycles, the mass change rate was less than or equal to 1.62%.
[0026] The coating samples obtained in this invention were subjected to ablation tests using an HEPJ-2 plasma flame spraying machine with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate after 120 s at 2200℃ was 0.16~1.12 mg / s. Based on the distance from the ablation center, the surface can be divided into three regions: the ablation center region, the transition region, and the edge region.
[0027] The composite coating developed and prepared in this invention is used for thermal protection of C / C composite materials. Attached Figure Description
[0028] Appendix Figure 1 Depend on Figure 1 (a) and Figure 1 (b) Composition, in which Figure 1 (a) is a scanning electron microscope image of the cross-section of the Si3N4 transition layer prepared in Example 1. Figure 1 (b) HfC prepared in Example 1 x N y Scanning electron microscope image of the cross-section of the TaC-B4C-SiC / Si3N4 coating.
[0029] Appendix Figure 2 The oxidation weight loss curves of Examples 1, 2, 3, and 4 at 1500°C are shown.
[0030] Appendix Figure 3 Depend on Figure 3 (a) Figure 3 (b) Figure 3 (c) and Figure 3 (d) Composition, which are the cross-sectional morphologies of the products obtained in Examples 1, 2, 3 and 4 after oxidation at 1500°C.
[0031] Appendix Figure 4 Depend on Figure 4 (a) Figure 4 (b) Figure 4 (c) and Figure 4 (d) The composition is the ablation macroscopic surface morphology of the products obtained in Examples 1, 2, 3 and 4 at 2200°C. Detailed Implementation
[0032] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments.
[0033] Example 1
[0034] A type of HfC that is resistant to ablation and thermal shock x N y The method for preparing a TaC-B4C-SiC / Si3N4 coating includes the following steps:
[0035] Step 1, Matrix Pretreatment
[0036] The C / C matrix (Φ10 mm × 10 mm, density 1.80 g / cm³) was used. 3 Sand the edges with sandpaper, chamfer the edges, ultrasonically clean with anhydrous ethanol, and dry for later use.
[0037] Step 2, Prepare Si3N4 transition layer
[0038] The raw materials for the Si3N4 transition layer, weighed according to the design composition, are mixed evenly to form a slurry suspension. Specifically, a phenolic resin solution is prepared by mixing phenolic resin and anhydrous ethanol at a mass ratio of 1:4. Then, a mixed powder of α-Si3N4, Si, Al2O3, and Y2O3 (mass ratio of α-Si3N4, Si, Al2O3, and Y2O3 in the mixed powder is 45:45:6:4; the particle size of the raw material α-Si3N4 powder is 1~3μm, the particle size of the raw material Si powder is 1~3μm, the particle size of the raw material Al2O3 powder is 1~10μm, and the particle size of the raw material Y2O3 powder is 1~10μm) is added to the phenolic resin solution and then evenly dispersed using a magnetic stirrer to form a slurry suspension. The mass ratio of the mixed powder of α-Si3N4, Si, Al2O3, and Y2O3 in the slurry suspension to the phenolic resin solution is 1:10.
[0039] The slurry was uniformly brushed onto the C / C substrate after the pretreatment in step 1. After drying, it was placed in an oven at 170°C for 5 hours to cure. Then, the cured sample was placed in Si3N4 embedding powder and kept at 1450°C in a nitrogen atmosphere for 2 hours to obtain a porous Si3N4 transition layer (the thickness of the transition layer is about 100 micrometers).
[0040] Step 3, prepare HfC x N y -TaC-B4C-SiC ceramic coating
[0041] HfC weighed according to the design composition x N y -The raw materials for the TaC-B4C-SiC ceramic coating are mixed evenly and prepared into a slurry suspension (raw material HfC) x N y The particle size of the powder is 1~3μm; the particle size of the raw material TaC powder is 1~3μm; the particle size of the raw material B4C powder is 1~3μm; the particle size of the raw material SiC powder is 1~3μm. Specifically, a phenolic resin solution is prepared by mixing phenolic resin and anhydrous ethanol at a mass ratio of 1:4, followed by ball milling for 12 hours and then sieving through a 200-mesh sieve to obtain HfC. x N y TaC, B4C, and SiC are added to the phenolic resin solution and then uniformly dispersed using a magnetic stirrer to form a slurry suspension. HfC... x N y The molar ratio of TaC and B4C is 1:1:1; HfC x N y The total mass ratio of TaC, B4C powders to SiC and phenolic resin solution is 1:1:2. The HfC used... x N y The carbon-nitrogen molar ratio in the powder is 64:36. The Si3N4 transition layer prepared in step 2 was completely immersed in the slurry suspension, immersing for 2 minutes each time, for a total of 3 immersions. Afterward, it was removed and dried, then cured in an oven at 160℃ for 5 hours. The cured sample was then pyrolyzed at 700℃ for 2 hours, and finally, the pyrolyzed sample was held at 1900℃ under a nitrogen atmosphere for 2 hours to obtain a smooth HfC. x N y -TaC-B4C-SiC ceramic coating.
[0042] The test results are as follows:
[0043] The prepared Si3N4 transition layer is as follows Figure 1 As shown in (a), the coating is tightly bonded to the substrate without cracks or other defects, indicating good physicochemical compatibility between the coating and the substrate. The cross-sectional morphology of the composite coating is as follows. Figure 1 As shown in (b), HfC can be observed. x N y There is a clear boundary between the TaC-B4C-SiC ceramic coating and the Si3N4 transition layer. The interface is tightly and naturally bonded, without obvious cracks, voids or other defects.
[0044] The sample was subjected to isothermal oxidation testing in air at 1500℃, and the sample was removed and weighed at regular intervals. The results showed that this HfC... x N y The TaC-B4C-SiC / Si3N4 coating can effectively protect C / C composite materials for 412 hours with a mass loss rate of only 0.98%.
[0045] The samples were placed in a tube furnace at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the samples, cooling them at room temperature for 5 minutes, and then weighing them; this cycle was repeated. After 43 thermal shocks, the weight loss rate was only 0.21%.
[0046] The coating sample was subjected to ablation testing using an HEPJ-2 plasma flame sprayer with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate after 120 s at 2200℃ was 0.16 mg / s.
[0047] Example 2
[0048] All other conditions are the same as in Example 1, except that:
[0049] Step 3, prepare HfC x N y -TaC-B4C-SiC ceramic coating
[0050] HfC weighed according to the design composition x N y -The raw materials for the TaC-B4C-SiC ceramic coating are mixed evenly and prepared into a slurry suspension (raw material HfC) x N y The particle size of the powder is 1~3μm; the particle size of the raw material TaC powder is 1~3μm; the particle size of the raw material B4C powder is 1~3μm; the particle size of the raw material SiC powder is 1~3μm. Specifically, a phenolic resin solution is prepared by mixing phenolic resin and anhydrous ethanol at a mass ratio of 1:4, followed by ball milling for 12 hours and then sieving through a 200-mesh sieve to obtain HfC. x N y TaC, B4C, and SiC are added to the phenolic resin solution and then uniformly dispersed using a magnetic stirrer to form a slurry suspension. HfC... x N y The molar ratio of TaC and B4C is 1:3:3; HfC x N y The total mass ratio of TaC, B4C powders to SiC and phenolic resin solution is 1:1:2. The HfC used... x N yThe carbon-nitrogen molar ratio in the powder is 64:36. The Si3N4 transition layer prepared in step 2 was completely immersed in the slurry suspension, immersing for 2 minutes each time, for a total of 3 immersions. Afterwards, it was removed and dried, then cured in an oven at 160℃ for 5 hours. The cured sample was then pyrolyzed at 700℃ for 2 hours, and finally held at 1950℃ under a nitrogen atmosphere for 2 hours to obtain a smooth HfC. x N y -TaC-B4C-SiC ceramic coating.
[0051] The test results are as follows:
[0052] The sample was subjected to isothermal oxidation testing in air at 1500℃, and the sample was removed and weighed at regular intervals. The results showed that this HfC... x N y The TaC-B4C-SiC / Si3N4 coating can effectively protect C / C composite materials for 227 hours with a mass loss rate of only 2.47%.
[0053] The samples were placed in a tube furnace at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the samples, cooling them at room temperature for 5 minutes, and then weighing them; this cycle was repeated. After 35 thermal shocks, the weight loss rate was only 1.15%.
[0054] The coating sample was subjected to ablation testing using an HEPJ-2 plasma flame sprayer with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate at 2200℃ for 120 s was 1.12 mg / s.
[0055] Example 3
[0056] All other conditions are the same as in Example 1, except that:
[0057] Step 3, prepare HfC x N y -TaC-B4C-SiC ceramic coating
[0058] HfC weighed according to the design composition x N y -The raw materials for the TaC-B4C-SiC ceramic coating are mixed evenly and prepared into a slurry suspension (raw material HfC) x N y The particle size of the powder is 1~3μm; the particle size of the raw material TaC powder is 1~3μm; the particle size of the raw material B4C powder is 1~3μm; the particle size of the raw material SiC powder is 1~3μm. Specifically, a phenolic resin solution is prepared by mixing phenolic resin and anhydrous ethanol at a mass ratio of 1:4, followed by ball milling for 12 hours and then sieving through a 200-mesh sieve to obtain HfC.x N y TaC, B4C, and SiC are added to the phenolic resin solution and then uniformly dispersed using a magnetic stirrer to form a slurry suspension. HfC... x N y The molar ratio of TaC and B4C is 3:1:1; HfC x N y The mass ratio of TaC, B4C mixed powder to SiC and phenolic resin solution is 1:1:2. The HfC used... x N y The carbon-nitrogen molar ratio in the powder is 64:36. The Si3N4 transition layer prepared in step 2 was completely immersed in the slurry suspension, immersing for 2 minutes each time, for a total of 3 immersions. Afterwards, it was removed and dried, then cured in an oven at 160℃ for 5 hours. The cured sample was then pyrolyzed at 700℃ for 2 hours, and finally held at 2000℃ under a nitrogen atmosphere for 2 hours to obtain a smooth HfC. x N y -TaC-B4C-SiC ceramic coating.
[0059] The test results are as follows:
[0060] The sample was subjected to isothermal oxidation testing in air at 1500℃, and the sample was removed and weighed at regular intervals. The results showed that this HfC... x N y The TaC-B4C-SiC / Si3N4 coating can effectively protect C / C composite materials for 327 hours with a mass loss rate of only 1.45%.
[0061] The samples were placed in a tube furnace at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the samples, cooling them at room temperature for 5 minutes, and then weighing them; this cycle was repeated. After 41 thermal shocks, the weight loss rate was only 0.46%.
[0062] The coating sample was subjected to ablation testing using an HEPJ-2 plasma flame sprayer with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate after 120 s at 2200℃ was 0.48 mg / s.
[0063] Example 4
[0064] All other conditions are the same as in Example 1, except that:
[0065] Step 2, Prepare Si3N4 transition layer
[0066] The raw materials for the Si3N4 transition layer, weighed according to the design composition, are mixed evenly to form a slurry suspension. Specifically, a phenolic resin solution is prepared by mixing phenolic resin and anhydrous ethanol at a mass ratio of 1:4. Then, a mixed powder of α-Si3N4, Si, Al2O3, and Y2O3 (mass ratio of α-Si3N4, Si, Al2O3, and Y2O3 is 50:40:6:4; particle size of α-Si3N4 powder is 1-3 μm, particle size of Si powder is 1-3 μm, particle size of Al2O3 powder is 1-10 μm, and particle size of Y2O3 powder is 1-10 μm) is added to the phenolic resin solution and then evenly dispersed using a magnetic stirrer to form a slurry suspension. The mass ratio of the mixed powder of α-Si3N4, Si, Al2O3, and Y2O3 in the slurry suspension to the phenolic resin solution is 1:10.
[0067] The slurry was uniformly brushed onto the C / C substrate after the pretreatment in step 1. After drying, it was placed in an oven at 170°C for 5 hours to cure. Then, the cured sample was placed in Si3N4 embedding powder and kept at 1450°C in a nitrogen atmosphere for 2 hours to obtain a porous Si3N4 transition layer (the thickness of the transition layer is about 100 micrometers).
[0068] Step 3, prepare HfC x N y -TaC-B4C-SiC ceramic coating
[0069] HfC weighed according to the design composition x N y -The raw materials for the TaC-B4C-SiC ceramic coating are mixed evenly and prepared into a slurry suspension (HfC). x N y The particle size of the powder is 1~3μm; the particle size of TaC powder is 3μm; the particle size of B4C powder is 3μm; the particle size of SiC powder is 3μm. Specifically, a phenolic resin solution is prepared by mixing phenolic resin and anhydrous ethanol at a mass ratio of 1:4, followed by ball milling for 12 hours and then sieving through a 200-mesh sieve to obtain HfC. x N y TaC, B4C, and SiC are added to the phenolic resin solution and then uniformly dispersed using a magnetic stirrer to form a slurry suspension. HfC... x N y The molar ratio of TaC and B4C is 1:2:2; HfC x N y The total mass ratio of TaC, B4C powders to SiC and phenolic resin solution is 1:1:2. The HfC used... x N yThe carbon-nitrogen molar ratio in the powder is 64:36. The Si3N4 transition layer prepared in step 2 was completely immersed in the slurry suspension, immersing for 2 minutes each time, for a total of 3 immersions. Afterwards, it was removed and dried, then cured in an oven at 160℃ for 5 hours. The cured sample was then pyrolyzed at 700℃ for 2 hours, and finally held at 2000℃ under a nitrogen atmosphere for 2 hours to obtain a smooth HfC. x N y -TaC-B4C-SiC ceramic coating.
[0070] The test results are as follows:
[0071] The sample was subjected to isothermal oxidation testing in air at 1500℃, and the sample was removed and weighed at regular intervals. The results showed that this HfC... x N y The TaC-B4C-SiC / Si3N4 coating can effectively protect C / C composite materials for 368 hours with a mass loss rate of only 1.14%.
[0072] The samples were placed in a tube furnace at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the samples, cooling them at room temperature for 5 minutes, and then weighing them; this cycle was repeated. After 42 thermal shocks, the weight loss rate was only 0.50%.
[0073] The coating sample was subjected to ablation testing using an HEPJ-2 plasma flame sprayer with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate after 120 s at 2200℃ was 0.77 mg / s.
[0074] Comparative Example 1
[0075] The other conditions are the same as in Example 1, except that the mass ratio of α-Si3N4, Si, Al2O3, and Y2O3 powders in step 2 is 70:20:6:4.
[0076] The test results are as follows:
[0077] The sample was subjected to isothermal oxidation testing in air at 1500℃, and the sample was removed and weighed at regular intervals. The results showed that this HfC... x N y The TaC-B4C-SiC / Si3N4 coating can effectively protect C / C composite materials for 107 hours with a mass loss rate of 3.11%.
[0078] The samples were placed in a tube furnace at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the samples, cooling them at room temperature for 5 minutes, and then weighing them; this cycle was repeated. After 30 thermal shocks, the weight loss rate was 3.56%.
[0079] The coating sample was subjected to ablation testing using an HEPJ-2 plasma flame sprayer with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate at 2200℃ for 60 s was 1.98 mg / s.
[0080] Comparative Example 2
[0081] The other conditions are the same as in Example 2, the only difference being: HfC in step 3. x N y The molar ratio of TaC and B4C is 1:4:4; HfC x N y The mass ratio of the mixed powder composed of TaC and B4C to the SiC and phenolic resin solution is 1:1:3.
[0082] The test results are as follows:
[0083] The sample was subjected to isothermal oxidation testing in air at 1500℃, and the sample was removed and weighed at regular intervals. The results showed that this HfC... x N y The TaC-B4C-SiC / Si3N4 coating can effectively protect C / C composite materials for 102 hours with a mass loss rate of 3.57%.
[0084] The samples were placed in a tube furnace at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the samples, cooling them at room temperature for 5 minutes, and then weighing them; this cycle was repeated. After 32 thermal shocks, the weight loss rate was 3.05%.
[0085] The coating sample was subjected to ablation testing using an HEPJ-2 plasma flame sprayer with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate at 2200℃ for 60 s was 2.93 mg / s.
[0086] Comparative Example 3
[0087] Other conditions are the same as in Example 3, except that in step 2, the mass ratio of α-Si3N4, Si, Al2O3, and Y2O3 powders is 30:60:6:4. In step 3, HfC... x N y The molar ratio of TaC and B4C is 1:4:4; HfCx N y The total mass ratio of the three powders (TaC, B4C, and SiC) to the phenolic resin solution is 1:2:3.
[0088] The test results are as follows:
[0089] The sample was subjected to isothermal oxidation testing in air at 1500℃, and the sample was removed and weighed at regular intervals. The results showed that this HfC... x N y The TaC-B4C-SiC / Si3N4 coating can effectively protect C / C composite materials for 87 hours with a mass loss rate of 4.91%.
[0090] The samples were placed in a tube furnace at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the samples, cooling them at room temperature for 5 minutes, and then weighing them; this cycle was repeated. After 25 thermal shocks, the weight loss rate was 4.16%.
[0091] The coating sample was subjected to ablation testing using an HEPJ-2 plasma flame sprayer with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate at 2200℃ for 60 s was 5.62 mg / s.
[0092] Comparative Example 4 Other conditions are the same as in Example 1, except that α-Si3N4 was not introduced when preparing the transition layer in step two; the specific preparation process is as follows: A type of HfC that is resistant to ablation and thermal shock x N y The method for preparing a TaC-B4C-SiC4 coating includes the following steps: Step 1, Matrix Pretreatment The C / C matrix (Φ10 mm × 10 mm, density 1.80 g / cm³) was used. 3 Sand the edges with sandpaper, chamfer the edges, ultrasonically clean with anhydrous ethanol, and dry for later use. Step 2, Prepare the transition layer The raw materials for the transition layer were weighed according to the design composition, mixed evenly, and a slurry suspension was prepared. Specifically, a phenolic resin solution was prepared by mixing phenolic resin and anhydrous ethanol at a mass ratio of 1:4. Then, a mixed powder of Si, Al2O3, and Y2O3 (with a mass ratio of 90:6:4 for Si, Al2O3, and Y2O3 in the mixed powder, obtained by ball milling for 12 hours and sieving through a 200-mesh sieve) was added to the phenolic resin solution. The mixture was then evenly dispersed using a magnetic stirrer to form a slurry suspension. The mass ratio of the mixed powder of Si, Al2O3, and Y2O3 in the slurry suspension to the phenolic resin solution was 1:10.
[0093] The slurry was uniformly brushed onto the C / C substrate after the pretreatment in step 1. After drying, it was placed in an oven at 170°C for 5 hours to cure. Then, the cured sample was kept at 1450°C for 2 hours under a nitrogen protective atmosphere to obtain the transition layer. Step 3, prepare HfC x N y -TaC-B4C-SiC ceramic coating HfC weighed according to the design composition x N y -The raw materials for the TaC-B4C-SiC ceramic coating are mixed evenly and prepared into a slurry suspension (raw material HfC) x N y The particle size of the powder is 1~3μm; the particle size of the raw material TaC powder is 1~3μm; the particle size of the raw material B4C powder is 1~3μm; the particle size of the raw material SiC powder is 1~3μm. Specifically, a phenolic resin solution is prepared by mixing phenolic resin and anhydrous ethanol at a mass ratio of 1:4, followed by ball milling for 12 hours and then sieving through a 200-mesh sieve to obtain HfC. x N y TaC, B4C, and SiC are added to the phenolic resin solution and then uniformly dispersed using a magnetic stirrer to form a slurry suspension. HfC... x N y The molar ratio of TaC and B4C is 1:1:1; HfC x N y The total mass ratio of TaC, B4C powders to SiC and phenolic resin solution is 1:1:2. The HfC used... x N yThe carbon-nitrogen molar ratio in the powder is 64:36. The matrix with the transition layer prepared in step 2 was completely immersed in the slurry suspension, immersing for 2 minutes each time, for a total of 3 immersions. Afterwards, it was removed and dried, then cured in an oven at 160℃ for 5 hours. The cured sample was then pyrolyzed at 700℃ for 2 hours, and finally, the pyrolyzed sample was kept at 1900℃ under a nitrogen atmosphere for 2 hours to obtain HfC. x N y -TaC-B4C-SiC ceramic coating.
[0094] The test results are as follows: The sample was subjected to isothermal oxidation testing in air at 1500℃, and the sample was weighed at regular intervals. The results showed that the coating could effectively protect the C / C composite material for only 316 hours, at which point the mass loss rate had already reached 2.19%.
[0095] The samples were placed in a tube furnace at 1500℃ for thermal shock testing. The experimental conditions were: heating at the specified temperature for 5 minutes, removing the samples, cooling them at room temperature for 5 minutes, and then weighing them; this cycle was repeated. After 30 thermal shocks, the weight loss rate reached 1.51%.
[0096] The coating sample was subjected to ablation testing using an HEPJ-2 plasma flame sprayer with the following parameters: power 48.75 kW, hydrogen flow rate 180 L / h, and argon flow rate 2000 L / h. The mass ablation rate at 2200℃ for 120 s was significantly higher than that of the coating obtained in Example 1, reaching as high as 8.27 mg / s.
Claims
1. A fire-resistant, ablation-resistant, and thermal shock-resistant composite coating, characterized in that: The fire-resistant, ablation-resistant, and thermal shock-resistant composite coating consists of a C / C matrix material, a Si3N4 transition layer, and HfC. x N y The structure consists of a TaC-B4C-SiC ceramic coating, with the following layers arranged outwards from the surface of the C / C substrate: a Si3N4 transition layer and an HfC layer. x N y -TaC-B4C-SiC ceramic coating; the raw materials used for the Si3N4 transition layer are α-Si3N4, Si, Al2O3, Y2O3, and phenolic resin solution, wherein the mass ratio of α-Si3N4, Si, Al2O3, and Y2O3 is 35~65:55~25:6:4; α-Si3N4, Si, Al2O3, and Y2O3 form a mixed powder, and the mass ratio of the mixed powder to the phenolic resin solution is 1:3~5; the HfC x N y The raw material used for the TaC-B4C-SiC ceramic coating is HfC. x N y TaC, B4C, SiC, and phenolic resin solution.
2. The fire-resistant, ablation-resistant, and thermal shock-resistant composite coating according to claim 1, characterized in that: The mass ratio of the raw materials α-Si3N4, Si, Al2O3, and Y2O3 used in the Si3N4 transition layer is 44~46:44~46:6:4; the mass ratio of the mixed powder composed of α-Si3N4, Si, Al2O3, and Y2O3 to the phenolic resin solution is 1:3.5~4.5, and the phenolic resin solution is composed of phenolic resin and anhydrous ethanol in a mass ratio of 1:3.5~4.
3. The fire-resistant, ablation-resistant, and thermal shock-resistant composite coating according to claim 2, characterized in that: The mass ratio of the raw materials α-Si3N4, Si, Al2O3, and Y2O3 used in the Si3N4 transition layer is 45:45:6:4; the mass ratio of the mixed powder composed of α-Si3N4, Si, Al2O3, and Y2O3 to the phenolic resin solution is 1:
4.
4. The fire-resistant, ablation-resistant, and thermal shock-resistant composite coating according to claim 1, characterized in that: The average particle size of the α-Si3N4, Si, Al2O3, and Y2O3 powders used is 1~10μm, and the purity is not less than 99.5%.
5. The fire-resistant, ablation-resistant, and thermal shock-resistant composite coating according to claim 1, characterized in that: HfC x N y The molar ratio of TaC and B4C is 1~3:3~1:3~1; HfC x N y The total mass ratio of the three powders (TaC, B4C, and SiC) to the phenolic resin solution is 1:1:1.5~3; the phenolic resin solution is composed of phenolic resin and anhydrous ethanol in a mass ratio of 1:3.5~4.
6. The fire-resistant, ablation-resistant, and thermal shock-resistant composite coating according to claim 5, characterized in that: The HfC used x N y In the powder, the carbon-nitrogen molar ratio is 54~72:46~28.
7. The fire-resistant, ablation-resistant, and thermal shock-resistant composite coating according to claim 6, characterized in that: The raw material used in the HfCxNy-TaC-B4C-SiC ceramic coating is HfC. x N y The molar ratio of TaC and B4C is 1:3:3; HfC x N y The total mass ratio of TaC, B4C powders to SiC and phenolic resin solution is 1:1:2; the HfC used... x N y The carbon-nitrogen molar ratio in the powder is 64:
36.
8. The fire-resistant, ablation-resistant, and thermal shock-resistant composite coating according to claim 6, characterized in that: The raw material used in the HfCxNy-TaC-B4C-SiC ceramic coating is HfC. x N y The molar ratio of TaC and B4C is 1:1:1; HfC x N y The mass ratio of the mixed powder composed of TaC and B4C to the SiC and phenolic resin solution is 1:1:2; the HfC used is... x N y The carbon-nitrogen molar ratio in the powder is 64:
36.
9. A method for preparing a fire-resistant, ablation-resistant, and thermal shock-resistant composite coating as described in any one of claims 1-8, characterized in that, Includes the following steps: Step 1, Matrix Pretreatment Sand the C / C substrate with sandpaper, chamfer the edges, ultrasonically clean with anhydrous ethanol and dry for later use. Step 2, Prepare Si3N4 transition layer The raw materials of the Si3N4 transition layer, weighed according to the design composition, are mixed evenly and a slurry suspension is prepared. Specifically, phenolic resin and anhydrous ethanol are prepared in a mass ratio of 1:4 to form a phenolic resin solution. Then, the α-Si3N4, Si, Al2O3 and Y2O3 mixed powder obtained by ball milling for 10-12 hours and sieving through a 200-mesh sieve is added to the phenolic resin solution and then evenly dispersed by a magnetic stirrer to form a slurry suspension. The slurry was uniformly brushed onto the C / C substrate after the pretreatment in step 1. After drying, it was placed in an oven at 150~200℃ for 3-6 hours to cure. Then, the cured sample was placed in Si3N4 embedding powder and kept at 1450~1650℃ in a nitrogen atmosphere for 2-3 hours to obtain a porous Si3N4 transition layer. Step 3, prepare HfC x N y -TaC-B4C-SiC ceramic coating HfC weighed according to the design composition x N y The raw materials for the TaC-B4C-SiC ceramic coating are mixed evenly to form a slurry suspension. The Si3N4 transition layer prepared in step 2 is immersed in the slurry suspension, removed, and dried. Then, it is cured in an oven at 150~200℃ for 3-6 hours. The cured sample is then pyrolyzed at 650~750℃ for 2-3 hours. Finally, the pyrolyzed sample is held at 1900℃~2100℃ in a nitrogen atmosphere for 2-3 hours to obtain a smooth HfC coating. x N y -TaC-B4C-SiC ceramic coating.
10. The application of a fire-resistant, ablation-resistant, and thermal shock-resistant composite coating as described in any one of claims 1-8, characterized in that: Used for thermal protection of C / C composite materials.
Citation Information
Patent Citations
Ablation-resistant thermal shock-resistant zirconium silicate-high-alumina glass / HTBS high-entropy ceramic coating as well as preparation method and application thereof
CN114605173A